2016
DOI: 10.18632/oncotarget.13976
|View full text |Cite
|
Sign up to set email alerts
|

The different outcomes between breast-conserving surgery and mastectomy in triple-negative breast cancer: a population-based study from the SEER 18 database

Abstract: Breast-conserving surgery (BCS) including radiotherapy (RT) has been demonstrated to provide at least equivalent prognosis to mastectomy in early-stage breast cancer. However, studies on triple-negative breast cancer (TNBC) patients are relatively scarce. The current population-based study aimed to investigate the distinct outcomes between BCS+RT and mastectomy in patients with TNBC. Utilizing the Surveillance, Epidemiology, and End Results (SEER) database, we enrolled 11,514 female TNBC cases diagnosed during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 23 publications
5
26
0
3
Order By: Relevance
“…Surgery was the main form of treatment (received by 96%) in patients with stage I-III TNBC. Patients underwent lumpectomy or mastectomy at rates of 63% and 33%, respectively, which demonstrates support for breast-conserving surgery comparable to 13 or greater than 8,33 that reported in other cohorts.…”
Section: Treatmentsupporting
confidence: 66%
See 1 more Smart Citation
“…Surgery was the main form of treatment (received by 96%) in patients with stage I-III TNBC. Patients underwent lumpectomy or mastectomy at rates of 63% and 33%, respectively, which demonstrates support for breast-conserving surgery comparable to 13 or greater than 8,33 that reported in other cohorts.…”
Section: Treatmentsupporting
confidence: 66%
“…[3][4][5] Population-based studies focused on TNBC are sparse and the majority address only clinical characteristics and outcomes. 3,[5][6][7][8][9][10][11][12][13][14][15][16] While older data report direct health-care costs for Ontario BC patients by cancer stage, 17 there are no published reports on resource utilization in an Ontario TNBC cohort by cancer stage. We sought to assess the occurrence, management, and resource utilization according to early versus de novo metastatic disease in Ontario women diagnosed with TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…Given these results, it is likely that PgR negativity should be taken into consideration when planning treatment. It is unlikely that reverting to more radical surgery in these patients will overcome the challenges of its poorer prognosis, as comparisons of breast‐conserving therapy versus mastectomy, and wider versus narrower margins in the most biologically aggressive triple‐negative breast cancers have demonstrated no difference in locoregional recurrence according to type of surgery performed. Patients with ER+PgR– disease should, however, be considered for more aggressive neoadjuvant or adjuvant therapy, including systemic chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the Surveillance, Epidemiology, and End Results (SEER) population-based database showed that breast-conserving surgery combined with radiation therapy was associated with better breast cancer-specific survival and OS compared to mastectomy. 18 On multivariate analysis, advanced nodal status and tumor size were significant factors for adverse survival. A Chinese study of 308 patients, with immunohistochemically-confirmed TNBC, showed that breast-conserving surgery was not associated with increased ipsilateral tumor recurrence compared to a non-TNBC subtype cohort.…”
Section: Discussionmentioning
confidence: 98%